Validity of the Lower Zab River Sediments for Road and Asphalt Works - Southwest of Kirkuk/Northern Iraq - Ibrahim Mustafa Hassan; Mohammed Rashid Abood; Lafta Salman Kadhim (Tikrit Journal of Pure Science, 2023)
In this study, a geotechnical assessment of gravel and sand deposits were conducted on both sides of the Lower Zab River in the southwest of Kirkuk Governorate/Northern Iraq. geologically the sediment related to Quaternary age and tectonically located at the  unstable zone. 5 samples were collected from the study area for the purpose of conducting various geotechnical tests on them and their validity for road works to the sub-base layer and the base layer for asphalt works.